Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah, Pendidikan, dan Kesehatan terhadap Indeks Pembangunan Manusia Kota dan Kabupaten di Provinsi Nusa Tenggara Barat - Gabi, Ainul; Wibowo, Muhammad Ghafur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research aims to analyze the influence of general allocation funds, local original income, education and health on the human development indeks of cities and districts in West Nusa Tenggara Province as the object of research over 5 years, namely 2018 - 2022. The research method used is panel data regression. The results of the study show that the General Allocation Fund states that there is a positive relationship with the Human Development Indeks but does not have a significant effect, local revenue has a positive and significant effect on the Human Development Indeks, government expenditure for the education function states that there is a significant negative relationship with the Human Development Indeks. and government expenditure on health functions stated that there was a negative and insignificant relationship with the human development indeks in West Nusa Tenggara Province.